Shifts in microbial diversity through land use intensity as drivers of carbon mineralization in soil - Tardy, Vincent; Spor, Aymé; Mathieu, Olivier; Lévèque, Jean; Terrat, Sébastien; Plassart, Pierre; Regnier, Tiffanie; Bardgett, Richard D.; van der Putten, Wim H.; Roggero, Pier Paolo; Seddaiu, Giovanna; Bagella, Simonetta; et al. (Soil biology & biochemistry, 2015)
Land use practices alter the biomass and structure of soil microbial communities. However, the impact of land management intensity on soil microbial diversity (i.e. richness and evenness) and consequences for functioning is still poorly understood. Here, we addressed this question by coupling molecular characterization of microbial diversity with measurements of carbon (C) mineralization in soils obtained from three locations across Europe, each representing a gradient of land management intensity under different soil and environmental conditions. Bacterial and fungal diversity were characterized by high throughput sequencing of ribosomal genes. Carbon cycling activities (i.e., mineralization of autochthonous soil organic matter, mineralization of allochthonous plant residues) were measured by quantifying 12C- and 13C-CO2 release after soils had been amended, or not, with 13C-labelled wheat residues. Variation partitioning analysis was used to rank biological and physicochemical soil parameters according to their relative contribution to these activities. Across all three locations, microbial diversity was greatest at intermediate levels of land use intensity, indicating that optimal management of soil microbial diversity might not be achieved under the least intensive agriculture. Microbial richness was the best predictor of the C-cycling activities, with bacterial and fungal richness explaining 32.2 and 17% of the intensity of autochthonous soil organic matter mineralization; and fungal richness explaining 77% of the intensity of wheat residues mineralization. Altogether, our results provide evidence that there is scope for improvement in soil management to enhance microbial biodiversity and optimize C transformations mediated by microbial communities in soil. •A moderate land use intensity may increase soil microbial diversity.•Microbial diversity is a good a predictor of the transformations of the C-cycling.•Changes in microbial diversity with land use intensity link to soil functioning.